Perceived needs of disease vector control programs: A review and synthesis of (sub)national assessments from South Asia and the Middle East. - Henk van den Berg; Kabirul Bashar; Rajib Chowdhury; Rajendra M Bhatt; Hardev Prasad Gupta; Ashwani Kumar; Shanmugavelu Sabesan; Ananganallur N Shriram; Hari Kishan Raju Konuganti; Akhouri T S Sinha; Mohammad Mehdi Sedaghat; Ahmadali Enayati; et al. (PLoS Neglected Tropical Diseases)
Systems for disease vector control should be effective, efficient, and flexible to be able to tackle contemporary challenges and threats in the control and elimination of vector-borne diseases. As a priority activity towards the strengthening of vector control systems, it has been advocated that countries conduct a vector-control needs assessment. A review was carried out of the perceived needs for disease vector control programs among eleven countries and subnational states in South Asia and the Middle East. In each country or state, independent teams conducted vector control needs assessment with engagement of stakeholders. Important weaknesses were described for malaria, dengue and leishmaniases regarding vector surveillance, insecticide susceptibility testing, monitoring and evaluation of operations, entomological capacity and laboratory infrastructure. In addition, community mobilization and intersectoral collaboration showed important gaps. Countries and states expressed concern about insecticide resistance that could reduce the continued effectiveness of interventions, which demands improved monitoring. Moreover, attainment of disease elimination necessitates enhanced vector surveillance. Vector control needs assessment provided a useful planning tool for systematic strengthening of vector control systems. A limitation in conducting the vector control needs assessment was that it is time- and resource-intensive. To increase the feasibility and utility of national assessments, an abridged version of the guidance should focus on operationally relevant topics of the assessment. Similar reviews are needed in other regions with different contextual conditions.